Nonequilibrium perturbative formalism and spectral function for the Anderson model - Hamasaki, M. (Condensed Matter Physics, 2007)
The present work is based on the nonequilibrium perturbative formalism. There the self-energies are derived
up to the fourth-order. Consequently, it proves that the nonequilibrium (real-time) perturbative expansion can
be connected with the Matsubara imaginary-time perturbative expansion for equilibrium. As the numerical
results, the Kondo resonance still disappears for bias voltage exceeding the Kondo temperatures, as observed
in experiments of two terminal systems. Дана робота використовує формалiзм нерiвноважної теорiї збурень. Отримано власнi енергiї до четвертого порядку теорiї збурень. Доведено, що нерiвноважнi розвинення в дiйсному часi можна пов’язати з рiвноважним мацубарiвським розвиненням в уявному часi.Щодо чисельних результатiв, то резонанс Кондо все ще зникає для зсувної напруги, яка перевищує температури Кондо, як i було спостережено в експериментах на двох граничних системах.